Comparison between 18 F-FDG PET/MRI and CT for distant metastases detection in restaging of locally advanced rectal cancer after neoadjuvant chemoradiotherapy - Sebastiano Milite; Francesco Vendemiati; Francesca Serani; Chiara Zanon; Quoc Riccardo Bao; Amalia Lupi; Alessandra Pulvirenti; Gaya Spolverato; Diego Cecchin; Emilio Quaia; Giulio Cabrelle; Filippo Crimì (Clinical and Translational Imaging, 2026)
Abstract Purpose To evaluate the diagnostic accuracy of total-body 18 F-FDG PET/MRI compared with contrast-enhanced CT in detecting distant metastases in patients with locally advanced rectal cancer (LARC) after neoadjuvant chemoradiotherapy (pCRT). Methods This retrospective study included patients with LARC treated with pCRT between 2016 and 2019. Both contrast-enhanced CT and 18 F-FDG PET/MRI were performed within 6–8 weeks after completion of pCRT. Two independent expert teams assessed the presence of hepatic, pulmonary, lymph node, and other distant metastases. Histopathology and/or radiological follow-up served as the reference standard. Sensitivity, specificity, accuracy, positive predictive value (PPV), negative predictive value (NPV), and AUC were compared between the two modalities. Results Metastases were confirmed in 17/51 patients (33.3%). PET/MRI showed significantly higher specificity (100% vs. 86%, p = 0.0313), PPV (100% vs. 45.5%, p = 0.0313), and accuracy (96.1% vs. 82.4%, p = 0.0156) for the detection of liver metastases compared with CT. No significant differences were found for other metastatic sites; however, PET/MRI demonstrated overall better performance for global M staging (84.3% vs. 80.4%) and for detecting metastases outside the liver, lungs, or distant lymph nodes (100% vs. 94.1%). Conversely, CT showed higher accuracy than PET/MRI for the detection of pulmonary metastases (88.2% vs. 84.3%) and distant lymph node metastases (96.1% vs. 90.2%). Conclusions 18 F-FDG PET/MRI performs significantly better than CT in detecting liver metastases and demonstrates higher accuracy for overall M staging and for identifying metastases outside the liver, lungs, or distant lymph nodes after pCRT in patients with LARC. Although CT appears more accurate for detecting lung and distant lymph node metastases, PET/MRI may improve overall restaging accuracy.